Open or closed? Understanding the molecular mechanisms and clinical implications of ADAMTS13's conformation - Quintijn Bonnez; Karen Vanhoorelbeke (HemaSphere, 2025)
Abstract By proteolyzing prothrombotic von Willebrand factor (VWF) multimers, ADAMTS13 (A Disintegrin And Metalloproteinase with ThromboSpondin type‐1 repeats, member 13) ensures balanced hemostasis and prevents microvascular thrombosis. ADAMTS13's conformational regulation is not only crucial for its enzymatic function, but also for the pathophysiology of thrombotic thrombocytopenic purpura (TTP). In the first part of this review, the unique structural features that keep ADAMTS13 in its closed, latent conformation are explored. Moreover, the recent structure predictions that propose a compactly folded model for closed ADAMTS13, and the molecular mechanisms involved in ADAMTS13's opening by its VWF substrate and other allosteric activators are discussed. Over the last decade, the changes in ADAMTS13's conformation in the context of immune‐mediated TTP (iTTP) were increasingly characterized, with open ADAMTS13 having emerged as a novel specific biomarker for acute and subclinical iTTP. Furthermore, open ADAMTS13 is gaining clinical attention to improve the prediction of early relapses during follow‐up of iTTP patients in remission. The specificity of the open ADAMTS13 biomarker for iTTP was retrospectively validated in patient cohorts with various thrombotic microangiopathies or hemostatic disorders, all dominantly presenting closed ADAMTS13. Hence, this review summarizes the molecular mechanisms that regulate ADAMTS13's conformation and links these with the clinical implications of ADAMTS13's open and closed conformations.